N′-(1,3-Benzothiazol-2-yl)benzenesulfonohydrazide: crystal structure, Hirshfeld surface analysis and computational chemistry - Baddeley, T. C.; Souza, Marcus V. N. de; Wardell, James L.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The asymmetric unit of the title compound, C13H11N3O2S2, comprises two independent molecules (A and B); the crystal structure was determined by employing synchrotron radiation. The molecules exhibit essentially the same features with an almost planar benzothiazole ring (r.m.s. deviation = 0.026 and 0.009 A˚ for A and B, respectively), which forms an inclined dihedral angle with the phenyl ring [28.3 (3) and 29.1 (3), respectively]. A difference between the molecules is noted in a twist about the N—S bonds [the C—S—N—N torsion angles = 56.2 (5) and 68.8 (5), respectively], which leads to a minor difference in orientation of the phenyl rings. In the molecular packing, A and B are linked into a supramolecular dimer via pairwise hydrazinyl-N—H...N(thiazolyl) hydrogen bonds. Hydrazinyl-N—H...O(sulfonyl) hydrogen bonds between A molecules assemble the dimers into chains along the a-axis direction, while links between centrosymmetrically related B molecules, leading to eightmembered {...HNSO}2 synthons, link the molecules along [001]. The result is an undulating supramolecular layer. Layers stack along the b-axis direction with benzothiazole-C—H...O(sulfonyl) points of contact being evident. The analyses of the calculated Hirshfeld surfaces confirm the relevance of the above intermolecular interactions, but also serve to further differentiate the weaker intermolecular interactions formed by the independent molecules, such as – interactions. This is also highlighted in distinctive energy frameworks calculated for the individual molecules.